Pediatric dental care in fanconi anemia : a case report = Cuidado dental pediátrico en paciente con anemia de Fanconi : reporte de un caso - Gaitán-Fonseca, César
Fanconi Anemia (FA) is an autosomal-recessive genetic disease that is linked to Chromosome X, which is reported in studies with pancytopenia, congenital malformations, and a predisposition to develop cancer. FA 1,360,000 births, and is a condition that occurs in heterozygous subjects in 0.5% of the population. In Mexico, there are, to our knowledge, no epidemiological data on FA, and it is thought that many cases are underdiagnosed. This document reports the clinical case of a patient diagnosed with FA who the cardinal signs of this rare pathology. The pediatric approach involved was performed with a preventive and restorative approach, in addition to the design and placement of a palatal shutter. After a follow-up of more than 12 months, a significant reduction in the recurrence of infections, such as otitis, tonsillitis, and pharyngitis, was observed, suggesting a positive influence of the use of the obturator. In turn with the latter, there was a lower need for transfusions, which may also be related to control of the foci of the infection. The pediatric approach employed in to patients with FA may have significant repercussions on both quality of life and on their patients' general systemic condition, although this is scarcely verifiable due to the rarity of this pathology.